Aerodynamic measurements of an airfoil with a spoiler - Gu, Weidong. (2009)
A rapidly deployed spoiler on the upper surface of a wing induces adverse lift and moment during aircraft landing. These adverse effects are associated with the strong starting vortex, which is caused by the shear flow at the spoiler tip and is located downstream of the deflected spoiler. This thesis presents an experimental study carried out on a NACA 0012 airfoil equipped with a rapidly erected spoiler in a low-speed wind-tunnel. Emphasis is placed on the reduction of the adverse lift and moment because not much on this aspect has been reported in the literature.